An Interventionist Dynamic Assessment Approach to College English Writing in China. Issue 1 (1st January 2023) - Tang, Youjun; Ma, Xiaomei
ABSTRACT: This article explores the value of dynamic assessment (DA) for college English writing (CEW), a required course for millions of students in China that typically enrolls 50 students in each class. An interventionist approach to DA, in which mediation and administration are standardized, was selected and supplemented with a construct-descriptor-based rating checklist as a writing assessment before and after an eight-week instruction phase. The DA group received graduated mediation that focused on the constructs and descriptors from the scale, while a control group received holistic corrections. Data were processed through ANOVA and MANCOVA revealing variable development concerning specific constructs but overall significantly greater improvement by the DA group. The results are interpreted according to the degree of change as indicative of the zone of proximal development. The value of the construct-driven scale and associated descriptors through the mediational process are also discussed. It is argued that interventionist DA is equipped to identify the components and processes within a construct, and in so doing offers the possibility of fine-tuning teachers' and learners' understanding of problem areas for individuals.